2002
DOI: 10.1103/physrevlett.88.092501
|View full text |Cite
|
Sign up to set email alerts
|

N2868i40: Magicity versus Superfluidity

Abstract: The neutron-rich (66,68)Ni have been produced at GANIL via interactions of a 65.9A MeV 70Zn beam with a 58Ni target. Their reduced transition probability B(E2;0(+)(1)-->2+) has been measured for the first time by Coulomb excitation in a (208)Pb target at intermediate energy. The B(E2) value for (68)Ni(40) is unexpectedly small. An analysis in terms of large scale shell model calculations stresses the importance of proton core excitations to reproduce the B(E2) values and indicates the erosion of the N = 40 har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
131
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 251 publications
(140 citation statements)
references
References 22 publications
(14 reference statements)
8
131
0
1
Order By: Relevance
“…The already known half-life of the first 2 + state in 66 Ni (T 1/2 = 0.8(2) ps, reported in Ref. [25]) was used to validate this method. A value of T 1/2 = 0.78(13) ps is obtained in this work, which is in prefect agreement with the literature value.…”
Section: Resultsmentioning
confidence: 99%
“…The already known half-life of the first 2 + state in 66 Ni (T 1/2 = 0.8(2) ps, reported in Ref. [25]) was used to validate this method. A value of T 1/2 = 0.78(13) ps is obtained in this work, which is in prefect agreement with the literature value.…”
Section: Resultsmentioning
confidence: 99%
“…[7]. However, mass measurements have showed that the shell gap at N = 40 is weak for 68 Ni [8], implying that the small B(E2) value does not indicate a subshell gap.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually assumed from its spectrum that 68 Ni is doubly-magic [43,44,45]. The excitation energy of its first 2 + state is, indeed, large and the B(E2; 0 + gs → 2 + 1 ) value small [46].…”
Section: Nimentioning
confidence: 99%